Storytelling Digital Pada Youtube Simamaung Podcast - Muhammad Fazri Chandra; Nenny Yulianita (Sean Institute, 2024)
In the digital era, narrative communication through podcasts has developed as an effective digital storytelling medium. This study analyzes how Simamaung Podcast utilizes narrative communication in building interesting stories and engagement with audiences. The method used is a qualitative approach with a case study on Simamaung Podcast, examining narrative elements that influence listener engagement and challenges in its implementation. The results of the study show that the use of narrative elements such as plot, characterization, and simple but distinctive language style, provides a strong appeal to the audience. Listeners are not only passive consumers, but also contribute to shaping the narrative through interactive features such as comments and online discussions. In addition, this podcast also strengthens the audience's digital literacy by presenting important issues such as club management and the dynamics of supporter culture in a reflective and critical manner. Simamaung Podcast utilizes digital media convergence to increase audience reach and engagement, especially through social media platforms such as Instagram and X.